What Will Happen to Plant Protection Product Regulation After Brexit?. (1st April 2017) - Baker, Sarah; Knight, Jon
In this article we will examine what the regulatory framework for plant protection products (PPPs) in UK agriculture and the wider supply chain might look like after exiting the EU. The current regulatory framework is determined by the EU Commission with subsequent approval for use in Member States being decided locally. The UK has a huge legislative task ahead replacing existing EU laws with equivalent UK ones in many areas. The regulation of pesticides is unlikely to be top of the agenda when it comes to considering changing regulation at the point of transition and it is, therefore, likely that the existing EU rules will be 'lifted and shifted' in the short to medium term, as part of 'The Great Repeal Bill', pending more fundamental reform in the longer term. The process of giving effect in UK law to EU regulations is likely to be complex, especially where those regulations confer responsibilities on particular EU bodies, which will no longer have jurisdiction once the UK exits. The Department for Exiting the EU (DExEU) asked departments to identify EU legislation relating to each department as either 'operable' (that is, could be lifted into UK law without significant amendment) or 'inoperable' (in need of reform before it could be used in the post-Brexit UK). The operable laws will work with a direct 'lift and shift' but the inoperable laws may require significant policy decisions to be made.